2020
DOI: 10.1055/s-0040-1716596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of Coenzyme Q10 as an Adjunct to Nonsurgical Periodontal Therapy and Its Effect on Crevicular Superoxide Dismutase in Patients with Chronic Periodontitis

Abstract: Objectives To assess the efficacy of coenzyme Q10 (CoQ10) as an adjunct to nonsurgical periodontal therapy and its effect on superoxide dismutase (SOD) in gingival crevicular fluid (GCF) in patients with chronic periodontitis (CP). Materials and Methods A total of 16 patients aged between 30 and 50 years having mild to moderate CP of both sexes having pocket depth of 5 to 7 mm in four nonadjacent interproximal sites were selected. The sites were randomized and divided into treatment and control groups. CoQ10 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Similarly, a study by Shaheen et al [78] reported topical application of CoQ10 resulted in a significant improvement in periodontal parameters compared to scaling and root planing alone. In contrast, in a study of 16 patients with periodontitis, topical application of CoQ10 significantly increased crevicular antioxidant status (quantified as superoxide dismutase), but did not significantly affect periodontal parameters (pocket depth, plaque index, gingival index) compared to scaling and root planing alone [79].…”
Section: Periodontal Diseasementioning
confidence: 75%
“…Similarly, a study by Shaheen et al [78] reported topical application of CoQ10 resulted in a significant improvement in periodontal parameters compared to scaling and root planing alone. In contrast, in a study of 16 patients with periodontitis, topical application of CoQ10 significantly increased crevicular antioxidant status (quantified as superoxide dismutase), but did not significantly affect periodontal parameters (pocket depth, plaque index, gingival index) compared to scaling and root planing alone [79].…”
Section: Periodontal Diseasementioning
confidence: 75%
“…[ 12 ] to test the efficacy of intrasulcular CoQ gel revealed a nonsignificant reduction for each clinical parameter on intergroup analysis between intrasulcular gel application combined with SRP and SRP alone. These results were also supported by Pranam et al .,[ 13 ] in which no statistically significant difference between clinical parameters was observed in both groups at all time intervals. They concluded that adjunctive use of CoQ 10 is not superior to SRP in the treatment of chronic periodontitis.…”
Section: Discussionmentioning
confidence: 87%
“…The total observation period ranged from one to six months. Eight studies tested CoQ10 in an FM [ 35 , 36 , 37 , 39 , 42 , 44 , 45 , 46 ], eight in an SM study design [ 38 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], and one did not clearly report the design [ 43 ]. Only three studies applied a placebo [ 45 , 48 , 49 ], and all other studies were controlled against SRP alone.…”
Section: Resultsmentioning
confidence: 99%